How economic ideas evolve: the impact of religion on the German and Italian welfare state - Hien, Josef (Cambridge studies in historical sociology, 2025)
How Economic Ideas Evolve offers a unique perspective on the development of political economies in Europe. With three major contributions, the book first establishes a link between religious, social, and economic ideas and the diverging development of political economies in Europe. Secondly, the work provides a historical sociological analysis of the contextual factors that influenced the development of religiously inspired socio-economic ideas. Chapters examine the impact of these ideas on economic and welfare institutions in Germany and Italy over three centuries. Lastly, the book goes beyond classic historical sociology to focus on the long-term developmental trajectories and impact of ideas on politics and policy. Thorough and expansive, How Economic Ideas Evolve contributes to the emerging scholarship of ideational historical sociology, broadening the toolkit of historical sociology to research the development and impact of socio-economic ideas and ideologies over long periods of time.